An Analysis of Early Outcomes of Knee Osteoarthritis Surgical Treatment - R. R. Ishtukov; T. B. Minasov; R. R. Yakupov; R. A. Saubanov; A. O. Ginoyan; I. I. Garipov; N. Z. Tatlybaeva (Креативная хирургия и онкология, 2019)
Introduction. Accounting for 33.3 % of all the cases of large joints osteoarthritis, the knee osteoarthritis is one of the most common diseases of the musculoskeletal system. It is a frequent cause of temporary and long-term disability. In this regard, the main goal of this study was to analyze early postoperative outcomes in such patients, as well as to establish a relationship between the predisposing factors and the development of the disease.Materials and methods. This paper presents a retrospective analysis of outcomes in 48 cases of arthroscopic treatment of the knee joint conducted at the Kuvatov Clinical Hospital. Patient population was predominantly female (36 cases), with the age averaging at 57. All the patients underwent arthroscopic surgery on the knee joint. The procedures included the resection of the damaged part of the meniscus, grinding and shaving off the damaged lateral or medial condyle hyaline cartilage, and debridement of the joint cavity. All the patients were assessed for pain using 10-point visual-analog scale of pain (pain VAS) prior to and two weeks after the surgery; the treatment efficacy was evaluated by the change in the number of points scored. The Leken algofunctional index was used for the assessment of the severity of gonarthrosis. The clinical symptoms of the disease were assessed prior to and two weeks after the arthroscopy.Results and discussion. We established that positive changes were clearly present two weeks following the surgery. Patients reported feeling better in general, lesser pain when walking, reduced swelling. In addition, the pain severity scores halved in comparison to the initial values.Conclusion. Our findings indicate that arthroscopic surgery is a clinically effective surgical treatment method. After the surgery, the patients demonstrated a drop in the pain intensity score, their knee joints felt less stiff, the motor functions of the knee joint were partially restored.